1995
DOI: 10.1055/s-2006-958058
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin, a Component ofMatricaria recutitaFlowers, is a Central Benzodiazepine Receptors-Ligand with Anxiolytic Effects

Abstract: The dried flower heads of Matricaria recutita L. (Asteraceae) are used in folk medicine to prepare a spasmolytic and sedative tea. Our fractionation of the aqueous extract of this plant led to the detection of several fractions with significant affinity for the central benzodiazepine receptor and to the isolation and identification of 5,7,4'-trihydroxyflavone (apigenin) in one of them. Apigenin competitively inhibited the binding of flunitrazepam with a Ki of 4 microM and had no effect on muscarinic receptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
186
2
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 325 publications
(209 citation statements)
references
References 3 publications
8
186
2
3
Order By: Relevance
“…However, it is also possible that the ability of apigenin to decrease the immobility in the forced swimming test may be simply due to the increased spontaneous motor activity such as psychostimulants, but Viola et al and Zanoli et al reported that at least apigenin doses up to 100 mg/kg did not increase the spontaneous motor activity. 13,15) Thus, the apigenin induced decrease in the immobility seems not to be mediated by stimulation of the overall motor activity of the animals. On the 478 Vol.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, it is also possible that the ability of apigenin to decrease the immobility in the forced swimming test may be simply due to the increased spontaneous motor activity such as psychostimulants, but Viola et al and Zanoli et al reported that at least apigenin doses up to 100 mg/kg did not increase the spontaneous motor activity. 13,15) Thus, the apigenin induced decrease in the immobility seems not to be mediated by stimulation of the overall motor activity of the animals. On the 478 Vol.…”
Section: Discussionmentioning
confidence: 93%
“…However, if apigenin decreased the GABA-activated Cl Ϫ currents, apigenin should exhibit an anxiogenic effect, but Viola et al and Salgueiro et al reported that apigenin exhibits anxiolytic activity in mice without any sedative or myorelaxant effects. 13,33) Thus, there are discrepancies in reporting the ability of apigenin to GABA activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations